Relationship Between Nurses’ End of Life Spiritual Care Knowledge and Attitudes With Religious Attitudes - Maryam Khandan; Aminreza Askarpoorkabir (Health, Spirituality and Medical Ethics)
Background and Objectives: Spiritual care is a part of holistic nursing care for end-of-life patients. One of the dimensions of this care is the religious dimension, which seems to be influenced by religious attitudes. Therefore, this study was conducted to determine nurses’ knowledge and attitude toward spiritual care for end-of-life patients and to investigate their relationship with religious attitudes in Pastor Hospital of Bam, southeast Iran. Methods: This descriptive-correlational study was conducted from November 2019 to May 2020. A total of 218 nurses were selected using the convenience sampling method. Data were collected using a reasearcher-made questionnaires containing four sections. Data analysis, which included descriptive and inferential statistics, was performed using SPSS software, version 24. Results: The mean scores of knowledge and attitude toward spiritual care were 13.62±3.36 and 73.94±8.52, respectively, reflecting a moderate level. The mean score of religious attitude was 133.86±19.37, reflecting a high level. Additionally, a significant relationship was observed between the scores of knowledge and attitude toward spiritual care, religious attitude, and some demographic variables (P<0.05). Conclusion: The current level of knowledge and attitude toward spiritual care is inadequate to provide holistic care for end-of-life patients. Considering the relationship between religious attitude and the main study variables can attract appropriate human resources.